2014
DOI: 10.15580/gjhpa.2014.1.012214054
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance Pattern of Earlobe Attachment amongst Nigerians

Abstract: Study on inheritance pattern of earlobe attachment in populations is scanty and reported to be unclear in populations where attempts have been made. In this study however, the inheritance pattern of earlobe attachment in a Nigerian population was investigated using 760 Nigerians from 200 families with 400 parents and 360 offspring within the ages of 5months-60years. Photographs of earlobe attachment of the subjects were taken and observed according to respective families. The result was analysed using Chi-test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 7 publications
2
15
1
1
Order By: Relevance
“…Hence, longer big toe might have expressed some level of dominance over shorter big toe, but this is not a clear indication of the dominance of the longer big toe. Although various researchers have expressed doubts that Morton's toe, like several other traits such as ear lobe attachment[41415] and nose shape,[5] which is believed to be transmitted in a Mendelian fashion, is rather based on more complex genetic models. [813] Kaplan[10] claimed that the relative length of the hallux and second toe is simply inherited with long hallux being recessive; nevertheless, this was not the case in this study; as the Mendelian Chi-square model show more conformance of dominance for the longer big toe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, longer big toe might have expressed some level of dominance over shorter big toe, but this is not a clear indication of the dominance of the longer big toe. Although various researchers have expressed doubts that Morton's toe, like several other traits such as ear lobe attachment[41415] and nose shape,[5] which is believed to be transmitted in a Mendelian fashion, is rather based on more complex genetic models. [813] Kaplan[10] claimed that the relative length of the hallux and second toe is simply inherited with long hallux being recessive; nevertheless, this was not the case in this study; as the Mendelian Chi-square model show more conformance of dominance for the longer big toe.…”
Section: Discussionmentioning
confidence: 99%
“…However, humans have numerous traits, but some traits are more frequently seen in population such as free-hanging earlobes, ability to roll their tongue, straight hairline, and right-handedness. [45] These traits are often expressed in different patterns, which are applicable in clinical and forensic investigations. [16]…”
Section: Introductionmentioning
confidence: 99%
“…Earlobe attachment (MIM: 128900 ) is often presented as an example of a readily observable Mendelian phenotype in educational materials 1 and continues to be studied as a Mendelian phenotype in the contemporary primary literature (for example, see Ordu et al. 2 ). Yet, as early as 1937, Wiener 3 pointed out that earlobe attachment is likely to be a polygenic trait exhibiting a continuous phenotypic distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that no two individuals are exactly the same; differences occurring in humans could be as a result of selection, migration and mode of inheritance (Bhasin et al, 1992). Inheritance is the mode of transmitting biological traits from parents to offspring through gene (Ordu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%